The "Healthy Akame!" community - government - university collaboration for health: a community-based participatory mixed-method approach to address health issue in rural Japan - Marinda Asiah Nuril Haya; Shuhei Ichikawa; Yukino Shibagaki; Akame Machijuu Genki Project Community Advisory Board; Hideki Wakabayashi; Yousuke Takemura (BMC, 2020)
Abstract Background Although Japan has a decentralized public health system, local governments have considered expert opinions over those of the community in decisions about public health programs. Differences in communities' interests may create gaps between health program objectives and implementation. We hypothesized that community-based participatory research (CBPR), which involves the community at every step, promotes effective program implementation and community empowerment. This study addressed the first step of CBPR, assessing community needs and developing tailored health program for a rural community in Japan. Methods In this sequential exploratory mixed-method study (qualitative followed by quantitative), we first formed a community advisory board (CAB) representing community organizations, city officials, and university researchers. The CAB conducted group discussions with community residents to identify the community's health issues and strengths. These group discussions were analyzed using thematic analysis, and the results were used to develop a questionnaire, which was subsequently sent to all households in the community to obtain priority scores for health issues and proposed action and to assess willingness to participate in community health program. The CAB then designed a program using the overall study results. Results Ten group discussions with 68 participants identified the following health issues: 1) diseases; 2) unhealthy behaviors; and 3) unsupportive environment. Nature, vacant lots, and local farms were considered local strengths. Of a total of 1470 households in the community, questionnaires were collected from 773 households. Cancer, lifestyle-related diseases, and cerebrovascular diseases were ranked as the most important health problems. Improving services and access to medical checkups, use of public space for exercise, local farming, and collaboration with the community health office were considered necessary to address these health problems. Considering feasibility and the availability of resources in the community, the CAB decided to focus on lifestyle-related diseases and designed activities centered on health awareness, nutrition, and exercise. These activities drew on community's strengths and were adapted to Japanese culture. Conclusions The community's priority health problem was closely related to the epidemiology of diseases. The CBPR approach was useful for identifying community's needs and for designing a unique community health program that made use of local strengths.